An Update on the Habitat Suitability Model of Dacrycarpus imbricatus (Blume) de Laub. and Its Conservation Status in Bali, Indonesia - Sutomo Sutomo; Muhammad Bima Atmaja; I Dewa Putu Darma; Rajif Iryadi; Aditya Hani; I Made Saka Wijaya; Made Maha Widyartha; Eddie van Etten (Universitas Gadjah Mada, 2023)
Dacrycarpus imbricatus provides essential ecosystem functions and various potential uses. Therefore, studying this distribution and conservation status in Bali Islands is crucial. The Habitat Suitability Model (HSM) and Geospatial Conservation Assessment Tool (GeoCAT) were used to predict this distribution and conservation status. The results showed changes in the predicted habitat suitability in 2050. Climate change conditions will impact the preferential habitat of the current location. The analysis classifies D. imbricatus as an endangered (EN) species in Bali. The model does not consider anthropogenic factors which change the land use/land cover. Therefore, more severe conservation efforts in Bali are needed for this species.